Types of Prophesiesֈ An innovative appoach - Uzunyan, Archpriest Drtad
While prophecy constitutes the most important part of the Bible, it has been, in our opinion, its least analyzed subject. The interpretation of the prophecies has produced the most extensive works in the Christian tradition. While the messages of the prophets have been analyzed in detail, the phenomenon of “prophesy” itself has received little attention. This study presents a brief but innovative approach to the subject of prophecy and its types. An approach from the Jewish tradition handed down from the Middle Ages to the present day is taken and only a summary is presented, while a new diversification is proposed with a different approach. In the first part of this study some studies from the Jewish and Armenian traditions about the types of prophesy are given with examples and examples of diversification are presented. In the second part, the subject of Practical Types of Prophecy, which is our proposition, is discussed and it is explained which types of prophecies should be examined. In conclusion we summarized our purpose and the main parts of the study. Несмотря на то, что пророчества составляют важнейшую часть Библии, они, на наш взгляд, являются ее наименее изученной темой. Толкованию пророчеств посвящены наиболее обширные работы в христианской традиции. В то время как послания пророков подробно анализировались, самому феномену "пророчества" уделялось мало внимания. В данном исследовании представлен краткий, но новаторский подход к теме пророчества и его типов. Взят подход из иудейской традиции, передаваемой от средневековья до наших дней, и представлено лишь краткое изложение, в то время как предложена новая диверсификация с иным подходом. В первой части исследования приводятся некоторые исследования из еврейской и армянской традиций о типах пророчества с примерами, а также примеры диверсификации. Во второй части обсуждается тема практических типов пророчества, которая является нашим предложением, и объясняется, какие типы пророчеств должны быть рассмотрены. В заключение мы подвели итог нашей цели и основных частей исследования. Թէեւ մարգարէութիւնը Աստուածաշունչի ամենակարեւոր մասն է, սակայն, մեր կարծիքով, եղած է ամենաքիչ վերլուծուած թեմաներէն մէկը: Մարգարէութիւններու մեկնութիւնը տուած է քրիստոնէական աւանդութեան ամենաընդարձակ աշխատութիւնները: Մինչ մարգարէներու պատգամները մանրամասնօրէն վերլուծուած են, «մարգարէութիւն» գաղափարը ինքնին քիչ ուշադրութեան արժանացած է: Այս ուսումնասիրութիւնը կը ներկայացնէ կարճ, բայց նորարարական մօտեցում՝ մարգարէութիւն թեմային եւ անոր տեսակներուն: Միջնադարէն մինչեւ մեր օրերը փոխանցուած հրէական աւանդութիւնէն մօտեցում մը կը ներկայացուի ամփոփ կերպով։ Ապա կ’առաջարկուի նոր տեսակաւորում՝ այլ մօտեցմամբ։ Այս ուսումնասիրութեան առաջին բաժնին մէջ տրուած են որոշ ուսումնասիրութիւններ հրէական և հայկական աւանդութիւններէն մարգարէութեան տեսակներու վերաբերեալ՝ օրինակներով և ներկայացուած են տեսակներու օրինակներ։ Երկրորդ բաժնին մէջ կը քննարկուի մարգարէութեան գործնական տեսակները, որ մեր առաջարկութիւնն է եւ կը բացատրի, թէ մարգարէութիւններու ինչ տեսակներու բաժնելով պէտք է քննուին։ Եզրափակութեան մէջ մենք ամփոփեցինք մեր նպատակը և ուսումնասիրութեան հիմնական մասերը:
Keywords: Theology